Relationship Between Procalcitonin Serum Level and Septic Patient Mortality in Dr. Saiful Anwar General Hospital, Malang - Agustin Iskandar; Deasy Ayuningtyas Tandio; Yeni Ayu Prihastuti (Intisari Sains Medis, 2020)
Background: Procalcitonin is more frequently analyzed for sepsis diagnosis. Procalcitonin shows a tendency to increase as sepsis worsens. However, published studies investigating the correlation between procalcitonin and mortality in an adult patient with sepsis in Indonesia were lacking. This research aims to know the relationship between procalcitonin and mortality in sepsis.Methods: A prospective cohort study was conducted in Dr. Saiful Anwar Public General Hospital, Malang, Indonesia from March to November 2018. During the study period, patients diagnosed with sepsis according to JAMA Sepsis-3 were tested for procalcitonin using Cobas e411 ECLIA method. The demographic and mortality data were acquired from the patients’ medical record. The statistical analysis was done with SPSS v.23, ? = 0.05.Results: From a total of 69 subjects, 43 did not survive (62.32%). The procalcitonin serum level is significantly higher in the non-survivors than the survivors (37.77 ng/mL vs. 3.07 ng/mL, p=0.016). The Spearman’s rank correlation test showed r=0.293 (p=0.015). Using a cutoff point of 2 ng/mL, the relative risk is 2.77 (0.950-8.078).Conclusion: There is a statistically significant weak relationship between procalcitonin and mortality, in which patients with procalcitonin equal or more than 2 ng/mL were 2.77 times more likely not to survive sepsis.